2013
DOI: 10.1556/jba.2.2013.005
|View full text |Cite
|
Sign up to set email alerts
|

Video game characteristics, happiness and flow as predictors of addiction among video game players: A pilot study

Abstract: Aims: Video games provide opportunities for positive psychological experiences such as flow-like phenomena during play and general happiness that could be associated with gaming achievements. However, research has shown that specific features of game play may be associated with problematic behaviour associated with addiction-like experiences. The study was aimed at analysing whether certain structural characteristics of video games, flow, and global happiness could be predictive of video game addiction. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 23 publications
7
95
1
6
Order By: Relevance
“…While MMORPGs have been consistently associated with IA (Kuss & Griffiths, 2012;Gentile et al, 2011), their likely positive effects in the areas of social interactions and facilitating educational learning have also been noted (Cole & Griffiths, 2007;De Freitas & Griffiths, 2011;Skoric & Kwan, 2011;Jones, Scholes, Johnson, Katsikitis, & Carras, 2014). Continuously increasing challenges, scoring, and immediate gratification in MMORPGs enable players to achieve a sense of self-actualization (Wan & Chiou, 2006), and this has been linked to IA (Hull, Williams & Griffiths, 2013).…”
Section: Massively Multiplayer Online Role-playing Games (Mmorpgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…While MMORPGs have been consistently associated with IA (Kuss & Griffiths, 2012;Gentile et al, 2011), their likely positive effects in the areas of social interactions and facilitating educational learning have also been noted (Cole & Griffiths, 2007;De Freitas & Griffiths, 2011;Skoric & Kwan, 2011;Jones, Scholes, Johnson, Katsikitis, & Carras, 2014). Continuously increasing challenges, scoring, and immediate gratification in MMORPGs enable players to achieve a sense of self-actualization (Wan & Chiou, 2006), and this has been linked to IA (Hull, Williams & Griffiths, 2013).…”
Section: Massively Multiplayer Online Role-playing Games (Mmorpgs)mentioning
confidence: 99%
“…This association can be explained by online satisfaction and immediate gratification due to addressing the gradually increasing level of challenges in MMORPGs (Choi & Kim, 2004;Hull et al, 2013;Wan & Chiou, 2006). More specifically, MMORPGs may trigger high emotional involvement and an increased need to spending time online (Gentile et al, 2011), and thus reinforcing IA.…”
Section: Mmorpgsmentioning
confidence: 99%
“…En relación a esto, los individuos que durante la experiencia de juego presentan una alteración de la conciencia temporal, están en riesgo de seguir jugando por un tiempo significativamente más largo, lo que también facilita el desarrollo de la adicción (Hull, Williams & Griffiths, 2013). Este estudio incluso advierte de la importancia de entrenar a los pacientes sobre la posibilidad de una mejor compresión sobre el tiempo dedicado al juego electrónico.…”
Section: Vulnerabilidad Individualunclassified
“…Regardless of existing debates, research has paid little attention to the role of flow experiences in videogame play, an area that still needs further investigation [29].…”
mentioning
confidence: 99%
“…However, the study conducted by Wan and Chiou [36] found flow experiences to be negatively associated with addictive inclination towards videogames, which led the authors to assert that flow experiences may not be the key psychological mechanism underlying videogame addiction. Online game flow has also been found to be a mediating factor between game motivations and videogame addiction [37], and a relatively recent study on videogame addiction and flow found that a particular factor of the flow experience (i.e., heightened levels of a sense of time being altered during play) significantly predicted videogame addiction [29].…”
mentioning
confidence: 99%